Building global partnerships through shared curricula for an MPH programme in India and Sri Lanka. Issue 9 (2nd September 2019) - Sathiakumar, Nalini; Tipre, Meghan; Wickremasinghe, Rajitha; Bhat, Vinod; Kadir, Muhammad Masood; Coggon, David; Pathemeswaran, Arunasalem; Kamath, Ramachandra; Arunkumar, G.; Fatmi, Zafar; Smith, Tamika L.; Pattanshetty, Sanjay M.; et al.
ABSTRACT: Objective: To design and implement a locally relevant competency based MPH programme. Methods: The demand for trained public health professionals in South Asia is enormous and growing, which created a unique opportunity for a Fogarty International Center-funded University of Alabama at Birmingham-South Asia [Aga Khan University, Pakistan; Manipal Academy of Higher Education, India; and University of Kelaniya, Sri Lanka] international research training in environmental and occupational health (ITREOH) programme. In 2009, a Master of Public Health (MPH) degree programme was designed using a combination of competencies developed by the Association of School of Public Health, the World Health Organization and the Centers for Disease Control and Prevention. Results: A competency based curriculum was developed with two specialty tracks in applied epidemiology and environmental and occupational health, emphasising applied practice and research. Conclusions: This is the most comprehensive skill-based MPH programme in the region, which positions each institution as a regional leader in public health training. The success of the programme has been amply demonstrated by placements of graduated MPH students in leadership roles in public, private and academic sectors within their countries.